Resiliensi Memoderatori Dampak Dari Stres Terhadap Gejala Psikosomatis Pada Remaja - Tanumihardjo, Vanni Nathasya; Suarya, Luh Made Karisma Sukmayanti (Peneliti.net, 2024)
Adolescence is a transitional period of development from childhood to adulthood where during this process, adolescents could be influenced by various factors such as stress. The inability of adolescents to cope with stress appropriately may result in numerous adverse outcomes, including psychosomatic symptoms. Resilience is the ability to respond positively while facing difficult life situations. The presence of resilience may help adolescence effectively resolve the negative outcomes of stress to not develop into psychosomatic symptoms. This is a quantitative research to figure out the role of stress on psychosomatic symptoms in adolescence while using resilience as a moderating variable. A total of 170 adolescents from Denpasar participated in this study. The tools used for data collection in this study are Resilience Scale, Stress Scale, Somatic Symptom Scale–8 (SSS-8), dan Psychosomatic Symptom Scale. The sampling technique used in this study is disproportionate stratified sampling, and Moderated Regression Analysis (MRA) was used for data analysis. The results from the MRA test revealed that stress has an individual coefficient value of 1,209 with a significance of 0,019 (p<0,05), which indicates that stress has a significant role in psychosomatic symptoms in adolescents. The moderation of resilience has a coefficient value of -0,005 with a significance of 0,318 (p>0,05), which indicates that resilience doesn’t have a significant role to strengthen or weaken the relationship between stress and psychosomatic symptoms in adolescents.